Deciphering the secrets of tumor-initiating cells in pancreatic ductal adenocarcinoma microenvironment: mechanisms and therapeutic opportunities - Zhou, Jun; Li, Jiajun; Lu, Haoyi; Hong, Yanggang (Frontiers in Immunology, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy characterized by poor prognosis, strong resistance to therapy, and a dense immunosuppressive tumor microenvironment (TME). A small subset of cells known as cancer stem cells (CSCs), or tumor-initiating cells (TICs), are increasingly recognized as key contributors to tumor initiation, metastasis, immune evasion, and treatment failure. These cells are defined by their self-renewal capacity, plasticity, and resistance to chemotherapeutic and targeted therapies. Pancreatic cancer stem cells (PaCSCs) are maintained by specific surface markers (CD44, CD133, EpCAM, ALDH1A1) and regulated by stemness-associated signaling pathways such as Wnt/β-catenin, Notch, Hedgehog, and TGF-β. Their survival is further enhanced by metabolic reprogramming, including shifts between glycolysis and oxidative phosphorylation and the activation of ROS-detoxifying enzymes. Importantly, PaCSCs reside in specialized niches formed by hypoxia, cancer-associated fibroblasts (CAFs), tumor-associated macrophages (TAMs), and extracellular matrix (ECM) components that together shield them from immune clearance and promote therapeutic resistance. This review outlines the molecular features and functional roles of PaCSCs, their interaction with the TME, and recent advances in targeting this CSC-stroma network. Promising therapeutic strategies, such as CAR-T/NK cell therapies, epigenetic inhibitors, and combination regimens with checkpoint blockade or stromal modulators, are discussed in the context of ongoing clinical trials. Targeting both CSCs and their supportive microenvironment is emerging as a necessary strategy to overcome resistance and improve clinical outcomes in PDAC.